2018
DOI: 10.1113/ep086951
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor‐dependent hyperexcitability of capsaicin‐sensitive bladder afferent neurones in mice with spinal cord injury

Abstract: Nerve growth factor (NGF) has been implicated as an important mediator in the induction of C-fibre bladder afferent hyperexcitability, which contributes to the emergence of neurogenic lower urinary tract dysfunction after spinal cord injury (SCI). In this study, we determined whether NGF immunoneutralization using an anti-NGF antibody (NGF-Ab) normalizes the SCI-induced changes in electrophysiological properties of capsaicin-sensitive C-fibre bladder afferent neurones in female C57BL/6 mice. The spinal cord wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Vizzard et al showed that the immunoreactivity of TrkA, which is a high‐affinity receptor for NGF, is predominantly expressed in C‐fiber afferent neurons and is increased in rat bladder afferent neurons after SCI . We recently reported that anti‐NGF antibody treatment in SCI mice reduced C‐fiber‐dependent NVCs during bladder filling and reduced hyperexcitability of TRPV1 positive, capsaicin‐sensitive C‐fiber bladder afferent neurons . It has also been reported that NGF‐activation of p38 MAPK increases the expression of TRPV1 receptor in DRG neurons .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Vizzard et al showed that the immunoreactivity of TrkA, which is a high‐affinity receptor for NGF, is predominantly expressed in C‐fiber afferent neurons and is increased in rat bladder afferent neurons after SCI . We recently reported that anti‐NGF antibody treatment in SCI mice reduced C‐fiber‐dependent NVCs during bladder filling and reduced hyperexcitability of TRPV1 positive, capsaicin‐sensitive C‐fiber bladder afferent neurons . It has also been reported that NGF‐activation of p38 MAPK increases the expression of TRPV1 receptor in DRG neurons .…”
Section: Discussionmentioning
confidence: 86%
“…13,14 We recently reported that anti-NGF antibody treatment in SCI mice reduced C-fiber-dependent NVCs during bladder filling and reduced hyperexcitability of TRPV1 positive, capsaicin-sensitive C-fiber bladder afferent neurons. 5,15,16 It has also been reported that NGF-activation of p38 MAPK increases the expression of TRPV1 receptor in DRG neurons. 8 Therefore, it is likely that p38 MAPK activation in bladder afferent pathways after SCI contributes to C-fiber afferent hyperexcitability at least in part via upregulation of TRPV1, leading to NVCs during the storage phase.…”
Section: Discussionmentioning
confidence: 95%
“…These results indicate that NGF plays an important role in the plasticity of TRP channel expression in bladder afferent neurons in SCI mice. We recently reported that anti-NGF Ab treatment, when administered using the same regimen as in this study, improved C-fiber-dependent DO, as indicated by a decrease in non-voiding contractions during bladder filling and the reduced hyperexcitability of capsaicin-sensitive C-fiber bladder afferent neurons in SCI mice [5, 11, 14]. Therefore, NGF-dependent changes in TRP channels, such as the changes in TRPV1, TRPC3, and TRPC6 found in this study, may contribute to the functional alterations of bladder function and bladder afferent activity that underlie SCI-induced DO.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, because this study showed that anti-NGF Ab treatment normalized the expression of TRPV1, TRPC3, and TRPC6, but not TRPC1 in SCI mice, NGF might be less important for the regulation of TRPC1 expression in SCI. Furthermore, our recent study also demonstrated that NGF plays an important role in the hyperexcitability of capsaicin-sensitive bladder afferent neurons due to the reduction of slow-decaying A-type K + (KA) channel activity in SCI mice [11]. Taken together, these current and previous results provide evidence that NGF-targeting therapies could be effective for the treatment of SCI-induced bladder afferent hyperexcitability and DO via the normalization of ion channels activity, such as that of KA channels [11], and the expression of TRP channels such as TRPV1, TRPC3, and TRPC6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation